Method for preparing ultrathin aluminosilicate glass
By preparing ultra-thin aluminosilicate glass, the problem of warping after chemical strengthening of float electronic glass substrates is solved, and the effect of reducing the warping degree and ensuring the quality of the glass is achieved.
Patent Information
- Application Number
- CN202411678831.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The float electronic glass substrate is warped after chemical reinforcement, which affects the fitting. As the product size increases, the warping value requirements become smaller and smaller, and the prior art has failed to effectively solve this problem.
A method of preparing ultra-thin aluminosilicate glass, including mixing SiO2, Al2O3, MgO, K2O, Na2O, ZrO2/Li2O raw materials, melting at high temperature to form a glass liquid, and forming a glass ribbon through a float process, followed by Annealing and chemical strengthening treatment are carried out to control the chemical strengthening warping value by adjusting the temperature of the spray area and the sodium/lithium content in the molten salt.
There is no need to grind and polish during the processing process, which reduces the warpage, ensures the quality of the glass, reduces processing costs, and reduces personnel and environmental risks during the chemical strengthening process.
Smart Images

Figure CN119461811A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of special glass manufacturing, and in particular to a method for preparing ultra-thin aluminosilicate glass. Background Art
[0002] Ultra-thin glass is also called ultra-thin electronic touch glass, with a thickness of 0.1-1.1mm. Ultra-thin glass has excellent hardness, transparency, heat resistance, electrical insulation, and airtightness. It has relatively stable mechanical and chemical properties under oxidation and light conditions. It can be used in tablet computers, mobile phones, wearable devices, car displays, and other displays, such as watches, 2.5D, 3D mobile phones, folding mobile phones, flexible e-books, curved TVs, etc.
[0003] Ultra-thin glass is mainly divided into substrate glass, cover glass, and touch glass according to its use and function. Among them, cover glass is mainly used to protect the functional parts inside the display device, and needs to have good mechanical strength (bending resistance, impact resistance, and drop resistance). In order to achieve the required mechanical properties, the cover glass processing process often requires chemical strengthening of the glass. At present, the production processes of cover glass substrates mainly include overflow method and float method. Compared with the overflow method, the float production process has the advantages of good flatness of the original sheet and large production capacity. However, since the glass substrate produced by the float method has a tin side and a non-tin side, after chemical strengthening, the glass is strengthened and warped, which affects the bonding. And as the size of current client products is getting larger and larger, the warping value requirements are getting smaller and smaller. The problem of large warping of float electronic glass substrates after chemical strengthening needs to be improved urgently.
[0004] Chinese patent application publication number: CN105837031B, discloses a high-strength chemically strengthened glass, at least one side of which contains an ion exchange layer, the ion exchange layer contains divalent alkaline earth metal ions that enter the high-strength chemically strengthened glass through an ion exchange chemical strengthening process; the ion exchange layer also contains monovalent alkali metal ions that enter the high-strength chemically strengthened glass through an ion exchange chemical strengthening process. The present invention also provides a method for strengthening a glass substrate, comprising the following steps: placing a glass substrate to be strengthened in an ion exchange salt bath, performing ion exchange strengthening, and obtaining the high-strength chemically strengthened glass. It can be seen that the above technical solution does not take into account the problem that chemical strengthening will cause the glass to warp and affect the performance of the glass. Summary of the invention
[0005] To this end, the present invention provides a method for preparing ultra-thin aluminosilicate glass, so as to overcome the problem of large warping of float electronic glass substrate after chemical strengthening in the prior art.
[0006] To achieve the above object, the present invention provides a method for preparing ultrathin aluminosilicate glass, comprising:
[0007] Step S1, mixing SiO2, Al2O3, MgO, K2O, Na2O, and ZrO2 / Li2O in proportion;
[0008] Step S2, sending the mixed raw materials into a glass melting furnace for high-temperature melting to form molten glass liquid;
[0009] Step S3, pouring the molten glass into a float tank filled with tin liquid to form a uniform glass ribbon on the surface of the tin liquid;
[0010] Step S4, cooling the glass ribbon in the tin bath until it solidifies to form a flat glass;
[0011] Step S5, annealing the solidified flat glass and performing chemical strengthening during the annealing process;
[0012] Step S6, when it is determined according to the enhanced warpage value that the chemical strengthening treatment does not meet the preset standard, a secondary determination is made according to the strength evaluation value whether the chemical strengthening treatment meets the preset standard;
[0013] Step S7, when it is determined that the chemical strengthening treatment does not meet the preset standard based on the strength evaluation value, the temperature of the spraying area is increased according to the difference between the strength evaluation value and the first preset strength evaluation value, or the sodium / lithium content in the molten salt is reduced according to the difference between the strength evaluation value and the second preset strength evaluation value;
[0014] Step S8, cutting the flat glass that has been chemically strengthened and meets the preset standards to obtain ultra-thin aluminosilicate glass.
[0015] Furthermore, the chemical strengthening process comprises:
[0016] Step S501, preheating the glass to a temperature close to the melting point of the molten salt;
[0017] Step S502, spraying a layer of molten salt on the non-tin surface of the glass to perform ion exchange;
[0018] Step S503, keeping the glass at a glass annealing point for a preset time;
[0019] Step S504, cooling the glass to room temperature.
[0020] Furthermore, the chemical strengthening includes ion exchange of potassium-sodium exchange and ion exchange of sodium-lithium exchange, wherein:
[0021] Performing ion exchange of potassium-sodium exchange for lithium-free glass;
[0022] For the lithium-containing glass, an ion exchange of sodium-lithium exchange is performed, and then an ion exchange of potassium-sodium exchange is performed.
[0023] Furthermore, the lithium-free glass raw material formula consists of the following parts by mass: SiO2 60-62%, Al2O3 13-15%, MgO 5.5-6.5%, K2O 4-6%, Na2O 13-15%, and ZrO2 0.6-0.8%.
[0024] Furthermore, the lithium-containing glass raw material formula consists of the following parts by mass: SiO2 60-64%, Al2O3 18-20%, MgO 1-3%, K2O 0-3%, Na2O 6-8%, and Li2O 4-6%.
[0025] Further, whether the chemical strengthening treatment meets the preset standard is determined according to the strengthening warpage value, wherein:
[0026] If the strengthening warpage value is less than the preset strengthening warpage value, it is determined that the chemical strengthening treatment meets the preset standard, and step S8 is executed;
[0027] If the strengthening warpage value is greater than or equal to the preset strengthening warpage value, it is determined that the chemical strengthening treatment does not meet the preset standard, and a secondary determination is made based on the strength evaluation value whether the chemical strengthening treatment meets the preset standard.
[0028] Further, a secondary determination is made as to whether the chemical strengthening treatment meets a preset standard based on the strength evaluation value, wherein:
[0029] If the strength evaluation value is less than the first preset strength evaluation value, it is determined that the chemical strengthening treatment meets the preset standard, and step S8 is executed;
[0030] If the strength evaluation value is greater than or equal to the first preset strength evaluation value and less than the second preset strength evaluation value, it is determined that the chemical strengthening treatment does not meet the preset standard, and the temperature of the spraying area is increased according to the difference between the strength evaluation value and the first preset strength evaluation value;
[0031] If the strength evaluation value is greater than or equal to the second preset strength evaluation value, it is determined that the chemical strengthening treatment does not meet the preset standard, and the sodium / lithium content in the molten salt is reduced according to the difference between the strength evaluation value and the second preset strength evaluation value.
[0032] Furthermore, the strength evaluation value is determined by the surface compressive stress value of the non-tin surface of the glass and the depth of the surface compressive stress layer.
[0033] Further, the temperature of the spraying area is increased according to the difference between the first intensity evaluation difference values, wherein:
[0034] If the first strength evaluation difference is less than a first preset strength evaluation difference, the temperature of the spraying area is increased to a corresponding value using a first temperature adjustment coefficient;
[0035] If the first strength evaluation difference is greater than or equal to the first preset strength evaluation difference and less than the second preset strength evaluation difference, the temperature of the spraying area is increased to a corresponding value using a second temperature adjustment coefficient;
[0036] If the first strength evaluation difference is greater than or equal to the second preset strength evaluation difference, the temperature of the spraying area is increased to a corresponding value using a third temperature adjustment coefficient;
[0037] The first strength evaluation difference is a difference between the strength evaluation value and the first preset strength evaluation value.
[0038] Furthermore, the adjustment range of the sodium / lithium content in the molten salt is positively correlated with the second strength evaluation difference, wherein the second strength evaluation difference is the difference between the strength evaluation value and the second preset strength evaluation value.
[0039] Compared with the prior art, the beneficial effect of the present invention is that the ultra-thin aluminosilicate glass prepared by the present invention does not need to be ground or polished during the processing, and the degree of warping can be reduced, thereby ensuring the quality of the glass and reducing the processing cost.
[0040] Furthermore, the present invention does not use a large amount of acidic gas in the chemical strengthening process, thereby reducing potential risks to personnel and the environment in glass production.
[0041] Furthermore, in the process of chemical strengthening, the present invention sets the temperature above the strain point of the glass to carry out ion exchange, and then anneals the stress generated by the ion exchange to eliminate the stress, thereby achieving the purpose of improving the chemical strengthening warpage, ensuring that there is no obvious interface or mutation between the composition and performance of the product, thereby ensuring the stability of the product. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is a flow chart of a method for preparing ultra-thin aluminosilicate glass according to an embodiment of the present invention;
[0043] Figure 2 This is a flow chart of an embodiment of the present invention for determining whether a chemical strengthening treatment meets a preset standard according to a strength evaluation value;
[0044] Figure 3 A flow chart of adjusting the temperature of the spraying area according to the first strength evaluation difference according to an embodiment of the present invention;
[0045] Figure 4 This is a flow chart of adjusting the sodium / lithium content in molten salt according to the second strength evaluation difference in an embodiment of the present invention. DETAILED DESCRIPTION
[0046] In order to make the objects and advantages of the present invention more clearly understood, the present invention is further described below in conjunction with embodiments; it should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0047] The preferred embodiments of the present invention are described below with reference to the accompanying drawings. It should be understood by those skilled in the art that these embodiments are only used to explain the technical principles of the present invention and are not intended to limit the protection scope of the present invention.
[0048] It should be noted that, in the description of the present invention, terms such as "up", "down", "left", "right", "inside" and "outside" indicating directions or positional relationships are based on the directions or positional relationships shown in the drawings. This is merely for the convenience of description and does not indicate or imply that the device or element must have a specific orientation, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the present invention.
[0049] In addition, it should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For those skilled in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0050] See also Figures 1 to 4 As shown, Figure 1 This is a flow chart of a method for preparing ultra-thin aluminosilicate glass according to an embodiment of the present invention; Figure 2 This is a flow chart of an embodiment of the present invention for determining whether a chemical strengthening treatment meets a preset standard according to a strength evaluation value; Figure 3 A flow chart of adjusting the temperature of the spraying area according to the first strength evaluation difference according to an embodiment of the present invention; Figure 4 This is a flow chart of adjusting the sodium / lithium content in molten salt according to the second strength evaluation difference in an embodiment of the present invention.
[0051] The method for preparing ultra-thin aluminosilicate glass according to an embodiment of the present invention comprises:
[0052] Step S1, mixing SiO2, Al2O3, MgO, K2O, Na2O, and ZrO2 / Li2O in proportion;
[0053] Step S2, sending the mixed raw materials into a glass melting furnace for high-temperature melting to form molten glass liquid;
[0054] Step S3, pouring the molten glass into a float tank filled with tin liquid to form a uniform glass ribbon on the surface of the tin liquid;
[0055] Step S4, cooling the glass ribbon in the tin bath until it solidifies to form a flat glass;
[0056] Step S5, annealing the solidified flat glass and performing chemical strengthening during the annealing process;
[0057] Step S6, when it is determined according to the enhanced warpage value that the chemical strengthening treatment does not meet the preset standard, a secondary determination is made according to the strength evaluation value whether the chemical strengthening treatment meets the preset standard;
[0058] Step S7, when it is determined that the chemical strengthening treatment does not meet the preset standard based on the strength evaluation value, the temperature of the spraying area is increased according to the difference between the strength evaluation value and the first preset strength evaluation value, or the sodium / lithium content in the molten salt is reduced according to the difference between the strength evaluation value and the second preset strength evaluation value;
[0059] Step S8, cutting the flat glass that has been chemically strengthened and meets the preset standards to obtain ultra-thin aluminosilicate glass.
[0060] Specifically, the chemical strengthening includes ion exchange of potassium-sodium exchange and ion exchange of sodium-lithium exchange, wherein:
[0061] Performing ion exchange of potassium-sodium exchange for lithium-free glass;
[0062] For the lithium-containing glass, an ion exchange of sodium-lithium exchange is performed, and then an ion exchange of potassium-sodium exchange is performed.
[0063] Specifically, the chemical strengthening process for lithium-free glass includes:
[0064] Step S501, heating the glass from room temperature to 380°C within 40 to 60 minutes;
[0065] Step S502, spraying a layer of molten salt on the non-tin surface of the glass to perform ion exchange, wherein the ion exchange temperature is 420° C. and the ion exchange time is 5 hours;
[0066] Step S503, keeping the glass at 380°C, the glass annealing point, for a preset time of 5 minutes;
[0067] Step S504, cooling the glass to room temperature within 40 minutes.
[0068] Specifically, step S502 in the chemical strengthening process of lithium-containing glass includes:
[0069] Sodium-lithium exchange, molten salt temperature is 440°C, ion exchange time is 90 minutes;
[0070] Potassium-sodium exchange, the molten salt temperature is 420°C, and the ion exchange time is 90 minutes.
[0071] Specifically, in the chemical strengthening process of lithium-containing glass, step S504 needs to quickly cool the glass to room temperature within 10 minutes. The specific time is not limited and can be determined according to actual production conditions.
[0072] Specifically, the lithium-free glass raw material formula consists of the following parts by mass: SiO2 60-62%, Al2O3 13-15%, MgO 5.5-6.5%, K2O 4-6%, Na2O 13-15%, and ZrO2 0.6-0.8%.
[0073] Specifically, the lithium-containing glass raw material formula consists of the following parts by mass: SiO2 60-64%, Al2O3 18-20%, MgO 1-3%, K2O 0-3%, Na2O 6-8%, and Li2O 4-6%.
[0074] Specifically, whether the chemical strengthening treatment meets the preset standard is determined according to the strengthening warpage value, wherein:
[0075] If the strengthening warpage value is less than the preset strengthening warpage value of 0.40 mm, it is determined that the chemical strengthening treatment meets the preset standard, and step S8 is executed;
[0076] If the strengthening warpage value is greater than or equal to the preset strengthening warpage value, it is determined that the chemical strengthening treatment does not meet the preset standard, and a secondary determination is made based on the strength evaluation value whether the chemical strengthening treatment meets the preset standard.
[0077] Specifically, a secondary determination is made as to whether the chemical strengthening treatment meets the preset standard according to the strength evaluation value, wherein:
[0078] If the strength evaluation value is less than the first preset strength evaluation value of 1.05, it is determined that the chemical strengthening treatment meets the preset standard, and step S8 is executed;
[0079] If the strength evaluation value is greater than or equal to the first preset strength evaluation value and less than the second preset strength evaluation value of 1.10, it is determined that the chemical strengthening treatment does not meet the preset standard, and the temperature of the spraying area is increased according to the difference between the strength evaluation value and the first preset strength evaluation value;
[0080] If the strength evaluation value is greater than or equal to the second preset strength evaluation value, it is determined that the chemical strengthening treatment does not meet the preset standard, and the sodium / lithium content in the molten salt is reduced according to the difference between the strength evaluation value and the second preset strength evaluation value.
[0081] Specifically, the process of determining the strength evaluation value by the surface compressive stress value of the non-tin surface of the glass and the depth of the surface compressive stress layer includes:
[0082] The first evaluation coefficient is assigned to the square root of the ratio of the surface compressive stress value to the surface compressive stress threshold to obtain the surface compressive stress evaluation value, wherein the first evaluation coefficient is 0.55 and the surface compressive stress threshold is 800 MPa;
[0083] The second evaluation coefficient is assigned to the surface compressive stress layer depth evaluation value after taking the square root of the ratio of the surface compressive stress layer depth to the surface compressive stress layer depth threshold, wherein the second evaluation coefficient is 0.42, and the surface compressive stress layer depth threshold is 40 μm;
[0084] The surface compressive stress evaluation value and the surface compressive stress layer depth evaluation value are added together and recorded as the strength evaluation value.
[0085] Specifically, it is characterized in that the temperature of the spraying area is increased according to the difference between the first intensity evaluation difference values, wherein:
[0086] If the first strength evaluation difference is less than the first preset strength evaluation difference of 0.02, the temperature of the spraying area is increased to a corresponding value using a first temperature adjustment coefficient of 1.01;
[0087] If the first strength evaluation difference is greater than or equal to the first preset strength evaluation difference and less than the second preset strength evaluation difference of 0.04, the temperature of the spraying area is increased to a corresponding value using a second temperature adjustment coefficient of 1.03;
[0088] If the first strength evaluation difference is greater than or equal to the second preset strength evaluation difference, the temperature of the spraying area is increased to a corresponding value using a third temperature adjustment coefficient of 1.05;
[0089] The first strength evaluation difference is a difference between the strength evaluation value and the first preset strength evaluation value.
[0090] Specifically, the adjustment range of the sodium / lithium content in the molten salt is positively correlated with the second strength evaluation difference, where
[0091] If the second strength evaluation difference is less than the third preset strength evaluation difference, the sodium / lithium content in the molten salt is reduced to a corresponding value using the first content adjustment coefficient of 0.99;
[0092] If the second strength evaluation difference is greater than or equal to the third preset strength evaluation difference and less than the fourth preset strength evaluation difference, the sodium / lithium content in the molten salt is reduced to a corresponding value using the second content adjustment coefficient of 0.97;
[0093] If the second strength evaluation difference is greater than or equal to the fourth preset strength evaluation difference, the sodium / lithium content in the molten salt is reduced to a corresponding value using the third content adjustment coefficient of 0.95;
[0094] The second strength evaluation difference is a difference between the strength evaluation value and the second preset strength evaluation value.
[0095] Specifically, the reinforced warpage is tested using a feeler gauge test to test the warpage at the four corners.
[0096] Specifically, the equipment used for the sodium / lithium content test is an X-ray fluorescence spectrometer ARL Perform'X.
[0097] Specifically, the CS value is the surface compressive stress value after chemical strengthening, and is measured using an Orihara FSM6000Le instrument.
[0098] Specifically, the DOL value is the depth of the surface compressive stress layer after chemical strengthening, and is measured using an Orihara FSM6000Le instrument.
[0099] Specifically, the CS30 value is the compressive stress value at a depth of 30 microns after chemical strengthening, and the equipment used for the test is the Orihara SLP2000 equipment;
[0100] Specifically, the DOL-Na value is the depth of the compressive stress layer after chemical strengthening, where Na and Li are replaced. The equipment used for the test is the Orihara SLP2000 equipment.
[0101] The present invention will be further described below in conjunction with embodiments:
[0102] Comparative Example 1
[0103] The embodiment of the present invention provides an ultra-thin aluminosilicate glass without lithium, wherein:
[0104] Molten salt composition (wt%): None;
[0105] Sodium / lithium content of the spraying solution: None;
[0106] Spraying area temperature (℃): None.
[0107] Example 1
[0108] The embodiment of the present invention provides an ultra-thin aluminosilicate glass without lithium, wherein:
[0109] Molten salt composition (wt%): KNO3;
[0110] Sodium / lithium content of the spraying solution (ppm): 0;
[0111] Spraying area temperature (℃): 600.
[0112] Example 2
[0113] The embodiment of the present invention provides an ultra-thin aluminosilicate glass without lithium, wherein:
[0114] Molten salt composition (wt%): KNO3 90%, NaNO3 10%;
[0115] Sodium / lithium content of the spraying solution (ppm): 27049;
[0116] Spraying area temperature (℃): 600.
[0117] Example 3
[0118] The embodiment of the present invention provides an ultra-thin aluminosilicate glass that does not contain lithium, wherein the molten salt composition (wt%) is: KNO3 70%, NaNO3 29%, NaOH 1%; the sodium / lithium content of the spraying solution (ppm): 84189;
[0119] Spraying area temperature (℃): 600.
[0120] Example 4
[0121] An embodiment of the present invention provides a lithium-free ultrathin aluminosilicate glass, wherein the molten salt composition (wt%) is: KNO3;
[0122] Sodium / lithium content of the spraying solution (ppm): 0;
[0123] Spraying area temperature (℃): 575.
[0124] Example 5
[0125] An embodiment of the present invention provides a lithium-free ultrathin aluminosilicate glass, wherein the molten salt composition (wt%) is: KNO3;
[0126] Sodium / lithium content of the spraying solution (ppm): 0;
[0127] Spraying area temperature (℃): 585.
[0128] Example 6
[0129] An embodiment of the present invention provides a lithium-free ultrathin aluminosilicate glass, wherein the molten salt composition (wt%) is: KNO3;
[0130] Sodium / lithium content of the spraying solution (ppm): 0;
[0131] Spraying area temperature (℃): 595.
[0132] The enhanced warpage values of Comparative Example 1, Example 1, Example 2, Example 3, Example 4, Example 5 and Example 6 were tested respectively, and the specific results are shown in Table 1 below:
[0133]
[0134] The surface compressive stress values and the depth of the surface compressive stress layer of the non-tin surface and the tin surface of Comparative Example 1, Example 1, Example 2, Example 3, Example 4, Example 5 and Example 6 were respectively detected. The specific results are shown in Table 2 below:
[0135]
[0136] According to the comparison between Comparative Example 1 and Examples 1-6 in Table 1 and Table 2, it can be seen that the present invention reduces the strengthening warpage value of the ultra-thin aluminosilicate glass without lithium by adjusting the sodium content of the spraying solution and the temperature of the spraying area in the preparation process. At the same time, the surface compressive stress value and the depth of the surface compressive stress layer of the non-tin surface are both reduced, which proves that the adjustment of the present invention reduces the glass warpage caused by chemical strengthening and thus improves the quality of the glass.
[0137] Comparative Example 2
[0138] An embodiment of the present invention provides an ultra-thin aluminosilicate glass containing lithium, wherein the molten salt composition (wt%) is: none;
[0139] Lithium content of the spraying solution: None;
[0140] Spraying area temperature (℃): None.
[0141] Example 7
[0142] An embodiment of the present invention provides an ultra-thin aluminosilicate glass containing lithium, wherein the molten salt composition (wt%) is: NaNO3;
[0143] Lithium content of the spraying solution (ppm): 0;
[0144] Spraying area temperature (℃): 555.
[0145] Example 8
[0146] The embodiment of the present invention provides an ultra-thin aluminosilicate glass containing lithium, wherein the molten salt composition (wt%) is: NaNO3 40%, KNO3 60%;
[0147] Sodium / lithium content of the spraying solution (ppm): 0;
[0148] Spraying area temperature (℃): 555
[0149] Example 9
[0150] The embodiment of the present invention provides an ultra-thin aluminosilicate glass containing lithium, wherein the molten salt composition (wt%) is: NaNO3 40%, KNO3 58%, LiNO3 2%; the sodium / lithium content of the spraying solution (ppm): 2013
[0151] Spraying area temperature (℃): 555
[0152] Example 10
[0153] The embodiment of the present invention provides an ultra-thin aluminosilicate glass containing lithium, wherein the molten salt composition (wt%) is: NaNO340%, KNO355%, LiNO35%; the sodium / lithium content (ppm) of the spraying solution is: 5033;
[0154] Spraying area temperature (℃): 555.
[0155] Embodiment 11
[0156] The embodiment of the present invention provides an ultra-thin aluminosilicate glass containing lithium, wherein the molten salt composition (wt%) is: NaNO3 40%, KNO3 60%;
[0157] Sodium / lithium content of the spraying solution (ppm): 0;
[0158] Spraying area temperature (℃): 540.
[0159] Example 12
[0160] The embodiment of the present invention provides an ultra-thin aluminosilicate glass containing lithium, wherein:
[0161] Molten salt composition (wt%): NaNO3 40%, KNO3 60%;
[0162] Sodium / lithium content of the spraying solution (ppm): 0;
[0163] Spraying area temperature (℃): 530.
[0164] The enhanced warpage values of Comparative Example 2, Example 7, Example 8, Example 9, Example 10, Example 11 and Example 12 were respectively tested, and the specific results are shown in Table 3 below:
[0165]
[0166] The surface compressive stress values and the depth of the surface compressive stress layer of the non-tin surface and the tin surface of Comparative Example 2, Example 7, Example 8, Example 9, Example 10, Example 11 and Example 12 were respectively detected. The specific results are shown in Table 4 below:
[0167]
[0168] According to the comparison between Comparative Example 2 and Examples 7-12 in Table 3 and Table 4, it can be seen that the present invention reduces the strengthening warpage value of the ultra-thin aluminosilicate glass containing lithium by adjusting the lithium content of the spraying solution and the temperature of the spraying area in the preparation process. At the same time, the surface compressive stress value and the depth of the surface compressive stress layer of the non-tin surface are both reduced, which proves that the adjustment of the present invention reduces the glass warpage caused by chemical strengthening and thus improves the quality of the glass.
[0169] So far, the technical solutions of the present invention have been described in conjunction with the preferred embodiments shown in the accompanying drawings. However, it is easy for those skilled in the art to understand that the protection scope of the present invention is obviously not limited to these specific embodiments. Without departing from the principle of the present invention, those skilled in the art can make equivalent changes or substitutions to the relevant technical features, and the technical solutions after these changes or substitutions will fall within the protection scope of the present invention.
[0170] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing ultrathin aluminosilicate glass, characterized in that: include: Step S1, mixing SiO2, Al2O3, MgO, K2O, Na2O, and ZrO2 / Li2O in proportion; Step S2, sending the mixed raw materials into a glass melting furnace for high-temperature melting to form molten glass liquid; Step S3, pouring the molten glass into a float tank filled with tin liquid to form a uniform glass ribbon on the surface of the tin liquid; Step S4, cooling the glass ribbon in the tin bath until it solidifies to form a flat glass; Step S5, annealing the solidified flat glass and performing chemical strengthening during the annealing process; Step S6, when it is determined according to the enhanced warpage value that the chemical strengthening treatment does not meet the preset standard, a secondary determination is made according to the strength evaluation value whether the chemical strengthening treatment meets the preset standard; Step S7, when it is determined that the chemical strengthening treatment does not meet the preset standard based on the strength evaluation value, the temperature of the spraying area is increased according to the difference between the strength evaluation value and the first preset strength evaluation value, or the sodium / lithium content in the molten salt is reduced according to the difference between the strength evaluation value and the second preset strength evaluation value; Step S8, cutting the flat glass that has been chemically strengthened and meets the preset standards to obtain ultra-thin aluminosilicate glass.
2. The method for preparing ultrathin aluminosilicate glass according to claim 1, characterized in that: The chemical strengthening process includes: Step S501, preheating the glass to a temperature close to the melting point of the molten salt; Step S502, spraying a layer of molten salt on the non-tin surface of the glass to perform ion exchange; Step S503, keeping the glass at a glass annealing point for a preset time; Step S504, cooling the glass to room temperature.
3. The method for preparing ultrathin aluminosilicate glass according to claim 2, characterized in that: The chemical strengthening includes ion exchange of potassium-sodium exchange and ion exchange of sodium-lithium exchange, wherein: Performing ion exchange of potassium-sodium exchange for lithium-free glass; For the lithium-containing glass, an ion exchange of sodium-lithium exchange is performed, and then an ion exchange of potassium-sodium exchange is performed.
4. The method for preparing ultrathin aluminosilicate glass according to claim 3, characterized in that: The lithium-free glass raw material formula consists of the following parts by mass: SiO2 60-62%, Al2O3 13-15%, MgO 5.5-6.5%, K2O 4-6%, Na2O 13-15%, and ZrO2 0.6-0.8%.
5. The method for preparing ultrathin aluminosilicate glass according to claim 4, characterized in that: The lithium-containing glass raw material formula consists of the following parts by mass: SiO2 60-64%, Al2O3 18-20%, MgO 1-3%, K2O 0-3%, Na2O 6-8%, and Li2O 4-6%.
6. The method for preparing ultrathin aluminosilicate glass according to claim 5, characterized in that: According to the strengthening warpage value, it is determined whether the chemical strengthening treatment meets the preset standard, wherein: If the strengthening warpage value is less than the preset strengthening warpage value, it is determined that the chemical strengthening treatment meets the preset standard, and step S8 is executed; If the strengthening warpage value is greater than or equal to the preset strengthening warpage value, it is determined that the chemical strengthening treatment does not meet the preset standard, and a secondary determination is made based on the strength evaluation value whether the chemical strengthening treatment meets the preset standard.
7. The method for preparing ultrathin aluminosilicate glass according to claim 6, characterized in that: A secondary determination is made as to whether the chemical strengthening treatment meets the preset standard according to the strength evaluation value, wherein: If the strength evaluation value is less than the first preset strength evaluation value, it is determined that the chemical strengthening treatment meets the preset standard, and step S8 is executed; If the strength evaluation value is greater than or equal to the first preset strength evaluation value and less than the second preset strength evaluation value, it is determined that the chemical strengthening treatment does not meet the preset standard, and the temperature of the spraying area is increased according to the difference between the strength evaluation value and the first preset strength evaluation value; If the strength evaluation value is greater than or equal to the second preset strength evaluation value, it is determined that the chemical strengthening treatment does not meet the preset standard, and the sodium / lithium content in the molten salt is reduced according to the difference between the strength evaluation value and the second preset strength evaluation value.
8. The method for preparing ultrathin aluminosilicate glass according to claim 7, characterized in that: The strength evaluation value is determined by the surface compressive stress value of the non-tin surface of the glass and the depth of the surface compressive stress layer.
9. The method for preparing ultrathin aluminosilicate glass according to claim 8, characterized in that: The temperature of the spraying area is increased according to the difference between the first intensity evaluation difference values, wherein: If the first strength evaluation difference is less than a first preset strength evaluation difference, the temperature of the spraying area is increased to a corresponding value using a first temperature adjustment coefficient; If the first strength evaluation difference is greater than or equal to the first preset strength evaluation difference and less than the second preset strength evaluation difference, the temperature of the spraying area is increased to a corresponding value using a second temperature adjustment coefficient; If the first strength evaluation difference is greater than or equal to the second preset strength evaluation difference, the temperature of the spraying area is increased to a corresponding value using a third temperature adjustment coefficient; The first strength evaluation difference is a difference between the strength evaluation value and the first preset strength evaluation value.
10. The method for preparing ultrathin aluminosilicate glass according to claim 9, characterized in that: The adjustment range of the sodium / lithium content in the molten salt is positively correlated with the second strength evaluation difference, wherein the second strength evaluation difference is the difference between the strength evaluation value and the second preset strength evaluation value.
Citation Information
Patent Citations
Method for reducing warping in chemical strengthening of glass and jig for strengthening
CN108516702A
Aluminosilicate glass and preparation method thereof
CN110028240A
Preparation method of high-transmittance high-strength ultrathin medium aluminum glass
CN112441740A
Low-warpage scratch-resistant sodium-aluminum-silicon glass as well as preparation method and application thereof
CN115028357A
Chemical strengthening method of raw glass sheet, low-warping-value strengthened glass, cover plate glass and display
CN116924699A
Cited By
Preparation method of high-precision ultrathin glass substrate
CN119850398A